Rationalizing the Permissibility of Mosque Decoration - Omer, Spahic (Journal of Islamic Architecture, 2016)
This paper discusses the subject of mosque decoration and some of the criteria which determine its permissibility or otherwise. Some aspects of the matter are somewhat sensitive and double-edged. Thus, the paper presents an objective, balanced and scientific account of the theme, steering clear of the sentimental aspects of the evidences often put forth by both the proponents and opponents of mosque decoration. The main thrusts of the paper are the issues pertaining to the legitimacy of decoration in general, the subject of the function of mosques vis-Ã -vis their decoration, as well as the broad guidelines that regulate mosque decoration emphasizing the decoration of the mihrab (praying niche) area and the qiblah wall. The paper concludes that in principle mosque decoration is permissible so long as it conforms to the requirements of the Islamic spirituality and the quintessence of genuine Islamic art and architecture.